Effect of laser or ultrasonic application on pneumatic crown removal - Ahmed Samir Awad Elsayed; Maged Elhakim; Maha Ahmed Taymour (Cairo : Ahmed Samir Awad Elsayed, 2013)
6 This study investigated the in vitro effect of ultrasonic instrumentation or laser application on the removal resistance of crowns cemented with two different cements (glass ionomer and zinc phosphate) removed by pneumatic crown remover after thermocycling and cyclic loading Thirty extracted human maxillary first molars were used Teeth selected with average crown length 7.5mm and 7mm width. The molars were mounted in 3/4-inch diameter plastic cylinders filled with epoxy. With the use of ahorizontal milling device the crown of each tooth was machined to receive a full-coverage cast restoration. Teeth were prepared with taper of approximately 8 degrees .The preparation is adjusted to be 5mm length and 6mm in width. Chamfered cervical margins were established until their axial walls were 0.5 mm away from the external outline. Crowns were cast in nickel chromium alloy using conventional lost wax casting technique. Castings in each subgroup were luted with two cements: zinc phosphate (spofa) Glass ionomer (kromoglass). The specimens were subjected to thermal aging simulating the oral conditions with mean low-temperature point was 6.60C (range 0{u2013}36 0C, median 5.00C) then they were subjected to mechanical aging (20000 cycles). Cylinders holding prepared teeth are placed in fixation device and pneumatic crown remover is used to remove the crowns. Timing is calculated in fractions of second . Data was summarized using mean and standard deviation for quantitative variables. Comparisons between groups were done using unpaired t test when comparing 2 groups and analysis of variance (ANOVA) with multiple comparisons post hoc test when comparing more than 2 groups. P-values less than 0.05 were considered as statistically significant and given star while P-values less than 0.01were considered as statistically highly significant and given two stars
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Prosthodontics
Issued also as CD
Keywords: Laser; Pneumatic crown remova; Ultrasonic application